Pembangunan E-Learning Menggunakan UML - Khairul Nizam, Saud (2002)

(untitled)
Electronic education is still one of the new method implemented in Malaysia nowadays. This new style of learning is foresee to be one of the learning method within few years with the support given by government to fuel the industry. With drastic changes in the industry, a standard should be set up as guidance for everyone involved to identify, determine and implement the electronic education. The execution of this standard will reduce the cost of implementation and this enhance the quality of educational background to the community. However, this standard can be extracted from models that have developed and the decision maker should have the knowledge to choose the best for them and their organization or their own community.